GIS and spatial statistics - Ryan, Louise (Henry Stewart Talks, 2007)
Introduction to GIS and its role in environmental epidemiology, Ways that GIS can be used to quantify environmental exposures, Statistical methods for analyzing spatial data, Examples where GIS has played a useful role
Archived at 2015/10/17